PSYCHO-EMOTIONAL STATE OF CHILDREN AND ADOLESCENTS WITH ACNE - O. A. Nosacheva; G. A. Karkashadze; L. S. Namazov-Baranova (Union of pediatricians of Russia, 2012)
The issue presents current views on the changes in the nervous system in children and adolescents with acne - shows the pathogenetic relationship of physical and psycho-emotional disorders. As part of a multidisciplinary approach the relationship between the onset and progression of acne and impaired emotional status were revealed. The levels of involvement in the psycho-emotional sphere of somatic pathology, as well as the basic methodology of the assessment and results of key studies of emotional status in patients with acne are presented.